BWISAGU: AN ETHNIC IDENTITY OF COLORS AND FLAVOUR OF THE BODOS OF KOKRAJHAR DISTRICT, ASSAM - Das, Dhira mani; Singh, Narendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Bwisagu is the springtime festival of the Bodo community that marks the beginning of the New Year. The Bodos belongs to the Indo-Mongolian family and they are one of the prominent indigenous tribe in Assam. The Bodos are predominantly agriculturists, and most of their religious activity, fairs, and festivals depend on agriculture. Most of the festive celebration is based on harvests, paddy planting, and the lunar calendar. Festivals are associated with dance, music, and food items, which are part of their cultural identity. The Bwisagu festival is associated with the Bihu festival of the Assamese people. There are many rituals and ceremonies associated with the Bwisagu festival that are performed before and after the celebration of festivals. Bwisagu festival holds significant importance among the Bodo community as one of the most revered celebrations. The primary focus of this research paper is to shed light on the festivities surrounding the Bwisagu festival and its evolving customs. Bwisagu, a spring festival is commemorated under different names by various Indian communities. This paper delves into the details of the Bwisagu festival, exploring aspects such as observance practices, its ties to religion and agriculture as well as the traditional attire, colour and flavour worn during this festive occasion in a comprehensive manner.